2017
DOI: 10.1371/journal.pone.0182867
|View full text |Cite
|
Sign up to set email alerts
|

PKC-epsilon deficiency alters progenitor cell populations in favor of megakaryopoiesis

Abstract: BackgroundIt has long been postulated that Protein Kinase C (PKC) is an important regulator of megakaryopoiesis. Recent contributions to the literature have outlined the functions of several individual PKC isoforms with regard to megakaryocyte differentiation and platelet production. However, the exact role of PKCε remains elusive.ObjectiveTo delineate the role of PKCε in megakaryopoiesis.Approach and resultsWe used a PKCε knockout mouse model to examine the effect of PKCε deficiency on platelet mass, megakary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…We previously showed that several tyrosine residues on Syk are phosphorylated in response to the GPVI agonist convulxin ( 8 , 31 ). Furthermore, we and others have demonstrated that both Syk Y519/520 and Y346 are phosphorylated downstream of CLEC-2 ( 32 , 33 ). Syk Y519/520 is located in the activation loop of Syk and appears to be crucial for Syk signaling ( 34 , 35 , 36 ).…”
supporting
confidence: 51%
“…We previously showed that several tyrosine residues on Syk are phosphorylated in response to the GPVI agonist convulxin ( 8 , 31 ). Furthermore, we and others have demonstrated that both Syk Y519/520 and Y346 are phosphorylated downstream of CLEC-2 ( 32 , 33 ). Syk Y519/520 is located in the activation loop of Syk and appears to be crucial for Syk signaling ( 34 , 35 , 36 ).…”
supporting
confidence: 51%
“…VEGF, Hypoxia, and Angiogenesis pathway, on the other hand, is involved in interaction between cancer and thrombosis 56 . Next, the TPO Signaling Pathway is associated with megakaryopoiesis- a process involving hematopoietic stem cells to generate megakaryocyte followed by the production of platelets 57 .…”
Section: Discussionmentioning
confidence: 99%
“…However, PKCε not only is responsible for the pain transition but also contributes to various physiological functions ( Chen and Tian, 2011 ; Kostyak et al, 2017 ). Its various roles present a particularly challenging problem, requiring clinicians to balance two competing interests: preventing the transition from acute to chronic pain and minimizing interference with physiological functions.…”
Section: Introductionmentioning
confidence: 99%